Theoretical Investigation of Photoisomerization Mechanisms of N-Salicilydenemethylfurylamine (SMFA) (Journal of Atomic and Molecular Sciences, 2015)
TExcited state reaction coordinates and the consequent energy profiles ofa new Schiff base, N-salicilydenemethylfurylamine (SMFA), have been investigatedwith the MP2 and CASSCF method. The potential energy profiles of the ground andthe lowest excited singlet state are calculated. The excited state potential energy profileshows a small barrier in the LIIC pathway of dissociation along the O-H stretchingcoordinate. This work suggests that there are two pathways in the photochemical reactionof SMFA. In one pathway, the photochemical product is the enol-type minimum.In the other pathway, the ESIPT reaction is observed and a excited state stationarystructure is reached. The trans-keto and cis-keto type structures will be obtained fromphotoexcitation of the enol isomer. Two conical intersections between the ground andexcited states act as the gates for nonadiabatic decay to the ground state.
Keywords: excited state reaction; ESIPT; photochromoic effect; SMFA; photoisomerization mechanism.